Pengaruh Metode Reward and Punishment Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas V SD Negeri 29 Pardomuan I Kecamatan Pangururan Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Ronna Madearni Munthe; Rida Gultom; Dame Taruli Simamora (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The purpose of this study is to determine how much influence the Reward And Punishment method has on the Learning Motivation of Christian Education for Class V Students of SD Negeri 29 Pardomuan I, Pangururan District, Samosir Regency for the 2023/2024 Learning Year. The research method used is quantitative research method with inferential statistics. The population is all grade V students of SD Negeri 29 Pardomuan I, Pangururan District, Samosir Regency, totaling 35 people. This study is a population study because the subjects are less than a hundred people so all of them are taken. Data was collected using a closed questionnaire of 40 items, namely 24 items for variable X and 16 items for variable Y. The results of data analysis showed that: 1) test analysis requirements: a) positive relationship test obtained value rxy = 0.517 > rtable(=0.05; IK=95%; n=35) which is 0.334 (0.517 > 0.334). b) A significant relationship test obtained a calculated value of 3.47 > the ttable price for an error of 5% of the two-party test and dk = n-2 = 35-2 = 33, then obtained ttable = 2.021 (3.47 > 2.021). 2) influence test: a) regression equation test, obtained regression equation Y ̂=41.81+0.20X. b) Regression coefficient of determination test (r²) = 26.7%. 3) test the hypothesis using the F test obtained Fcalculate = 11.58 and obtained Ftabel = (=0.05, dk numerator k k = 18, dk denominator = n-2=35-2=33) = 1.51 then Fcalculate > Ftable which is 11.58 > 1.51. So it can be concluded that there is a positive and significant influence of the Reward And Punishment Method on the Learning Motivation of Christian Education for Class V Students of SD Negeri 29 Pardomuan I, Pangururan District, Samosir Regency for the 2023/2024 Learning Year.